OPTIMIZATION OF BLENDED LEARNING WITH OBS STUDIO ASSISTED BY DOMINO MULTIPLICATION MEDIA - Riski, Yunia Tiara; Musa, Juvelyn Doria; Huda, Muhammad Nur; Sukartiningsih, Wahyu (Universitas Pendidikan Indonesia, 2022)
The purpose of this study was to improve student learning achievement by optimizing Blended Learning with Open Broadcaster Software (OBS) assisted by Domino multiplication media for fifth grade students at the Indonesian School of Davao. The learning achievement in question is student activities and learning outcomes. This type of research is classroom action research with two cycles, each cycle is consisting one meeting. Each meeting consisting four stages, namely planning (planning), action (acting), observation (observing), and reflection (reflecting). The data analysis technique used were quantitative and qualitative analysis techniques. The results showed that student activity increased in each successive cycle obtaining a mean score of 2.97 (good): 3.18 (very good). Student learning outcomes increase in each cycle. In cycle 1 the classical completeness was 75% with an average value of 82.5. Cycle II classical completeness was 87.5% with an average value of 87.5. Cycle II data shows that classical completeness has reached the target of 85%, which was 87.5%. The conclusion of this research is that optimizing Blended Learning with Open Broadcaster Software assisted by Domino Multiplication Media can improve Learning Achievement in Grade V Mathematics Learning at the Indonesian School of Davao Philippines